Kontribusi IUCN dalam Mendukung Program Konservasi Alam di Taman Nasional Serengeti - Arie Kusuma Paksi; Talitha Ofira Belani; Amalia Nurul Hutami (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
Serengeti National Park, considered one of the most famous and significant wildlife reserves globally, where natural beauty and unparalleled scientific value converge, is experiencing a decline in habitat quality year after year. Despite the natural wealth within the Serengeti, various issues threaten wildlife species and habitats. These problems include the rapid growth of the human population, poverty, illegal hunting, and the drying up of the Mara River due to climate change. The international community has authorized the International Union for Conservation of Nature (IUCN) to develop ideas for conservation efforts. The organization illustrates how biodiversity is fundamental in addressing some of the world’s most significant challenges, such as tackling climate change, achieving sustainable energy, improving human well-being, and building a green economy. The study aims to narrate the IUCN’s role in executing environmental protection processes, intending to ensure that environmental goals hold the same importance as social goals through sustainable development. This study employs a qualitative approach, utilizing provided facts to create a detailed account of an incident. Additionally, secondary data is incorporated, involving the use of existing information. The results indicate that, despite various actions taken by the IUCN, the organization has not maximally resolved issues in the Serengeti, and several problems are still ongoing.